Wisma AIA Bhd Ipoh / Muhammad Aqil Hanis Talha... [et al.] - Talha, Muhammad Aqil Hanis; Abdul Hamid Al-Mahdali, Muhammad Ali Mahdalie; Hasni, Muhammad Syafiq; Nadlan, Muhd Faizul; Zarqa Zakaria, Siti Nurqamarina (2016)
Wisma AIA Bhd. does not have many problems due to facility management is concerned with the satisfaction and comfort to the tenants or occupants in the building itself. This will be seen from the physical view where the building maintenance management and building performance will increase the building market value. This is because their Property Administration always monitors this building properly. In addition, the Property Administration in this building monitor all AIA Bhd. building in Northern of Malaysia in maintenance department. From our observation, we had identified that there is no enough facilities for disabled person such as covered walkway for OKU, dot-type tactile tiles and line-type tactile tile for the blind. The facilities that provided by Wisma AIA Bhd is just toilet for disabled people and one special walkway at the main entrance. These facilities are important for disabled person to give comfort that visiting the building and also improper maintenance team in the building should give an attention. Space Audit of the building should be done to identify the weakness and solves space issues. Next, building maintenance status is considered poor based on the action taken to repair the defect. The defect might be small but if the defect is exposing in a long time, without any remedy action or immediate remedy action, it will make the condition of the building become worst. If they detect a failure or damage, they have to delay the remedial action due to limited budget. To maintain the building on time, the building needs extra income. Thus, they have to generate extra source of income or allocate bigger source for income. The presence budget allocation is only for schedule maintenance, and focus on mechanical equipment. Lastly, façade is the main identity of the building and bring a lot of value. Condition of the building façade need to be care. Defect need to repair, preventive and corrective maintenance need to be carry out. If require, repaint the building with new paint.